PH and Antimicrobial Activity of Portland Cement Associated with Different Radiopacifying Agents. (16th October 2012) - Guerreiro-Tanomaru, Juliane Maria; Cornélio, Ana Lívia G.; Andolfatto, Carolina; Salles, Loise P.; Tanomaru-Filho, Mário
Abstract : Objective . The aim of this study was to evaluate the antimicrobial activity and pH changes induced by Portland cement (PC) alone and in association with radiopacifiers. Methods . The materials tested were pure PC, PC + bismuth oxide, PC + zirconium oxide, PC + calcium tungstate, and zinc oxide and eugenol cement (ZOE). Antimicrobial activity was evaluated by agar diffusion test using the following strains: Micrococcus luteus, Streptococcus mutans, Enterococcus faecalis, Pseudomonas aeruginosa, and Candida albicans . After 24 hours of incubation at 37°C, inhibition of bacterial growth was observed and measured. For pH analysis, material samples (n = 10 ) were placed in polyethylene tubes and immersed in 10 mL of distilled water. After 12, 24, 48, and 72 hours, the pH of the solutions was determined using a pH meter. Results . All microbial species were inhibited by the cements evaluated. All materials composed of PC with radiopacifying agents promoted pH increase similar to pure Portland cement. ZOE had the lowest pH values throughout all experimental periods. Conclusions. All Portland cement-based materials with the addition of different radiopacifiers (bismuth oxide, calcium tungstate, and zirconium oxide) presented antimicrobial activity and pH similar to pure Portland cement.